Better feed oat for cattle - Rossnagel, Brian; Zatorski, Tom; Racz, Vern; McKinnon, John; Chritstensen, David (MTT, 2004)
Milling and feed grain quality improvement are cornerstones of the Crop Development Centre oat improvement program. Oat quality improvement focuses on food use, but the majority of world production is fed to ruminant livestock, thus feed quality improvement deserves consideration. This is especially true in western Canada where the feed market sets the base price for oat, and without assurance of an alternative feed market, growers cannot economically consider growing oat. While what makes a good food oat generally makes a good feed oat, specific feed value improvements can be made. Breeding to improve feed quality must consider physical and chemical traits, target livestock class and quality of competing grains. This generally means improving oat energy density for ruminants (especially cattle in Canada) versus that from barley, maize or wheat. Oat is considered the poorest grain because of high levels of indigestible fibre (hull) and low energy density. Improved physical quality, concentrating on increased groat/hull, is a major goal and has greatly improved the feed value of recent CDC varieties. Simultaneous selection for low % hull and greater uniformity, plumpness, bulk density (Test wt.) and size (MKW) resulted in varieties like CDC Dancer with significant genetic improvement in % groat and uniformity resulting in lower ADF, NDF, lignin and crude fibre and increased starch. Combining this improved physical quality with the LLH (low acid detergent hull) trait reported in 2000 (Thompson et al, 2000), where hull digestibility for ruminants is doubled, and increasing energy density by introducing greater groat fat (HOG), the LLH-HOG feed oat project to produce a whole grain oat for cattle with feed value of barley and approaching that of maize has been developed. Initial feed trial results demonstrate that LLH adds 6.5 7.5% energy and HOG adds 2.0 2.5% versus regular oat, with a total LLH-HOG energy of 84 84.5 % TDN versus 82.5% for barley. On an economic basis this translates to LLH-HOG oat valued at $129/tonne in western Canada versus barley at $103 and maize at $110. LLH-HOG selections, entered in the 2004 Western Canadian Co-operative Oat trials, should be considered for registration and release in 2006. Thompson, R.K., et al. 2000. Canadian Journal of Animal Science 80:377- 379.
Keywords: Ka; oat; ruminant; feed; LLH-HOG; fibre; energy; lignin